(untitled) (Web of Teachers: Inderscience Research, 2024)
This article explores the semantic intricacies of tongue twisters in both English and Uzbek languages. Tongue twisters are linguistic phenomena known for their challenging phonetic structures, often used for amusement and linguistic exercises. Through semantic analysis, this study delves into the underlying meanings and cultural nuances embedded within tongue twisters, shedding light on how these linguistic constructs reflect the characteristics of their respective languages and cultures. The comparative analysis between English and Uzbek tongue twisters offers insights into the diverse linguistic landscapes and highlights the importance of cultural context in understanding language play.